PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN PADAPT. CIOMAS ADISATWAPALEMBANG - Fachrun Al Rasyid; Roswaty Roswaty; M. Kurniawan (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this study was to find how the effect of democratic leadership style on employee job satisfaction was. The object of the study was PT. Ciomas Adisatwa Palembang. This study used qualitative and quantitative methods consisting of two variables: democratic leadership style as an independent variable and employee job satisfaction as a dependent variable. The types of data used were primary and secondary data. Techniques for collecting the data were interview, observation, questionnaire, documentation and literature study. In analyzing the data, simple regression analysis and t-test were used. The result of the study showed that the democratic leadership style partially had a significant effect on employee job satisfaction. It could be seen from the R which was 0.626 that means there was a good correlation between the democratic leadership style and very good employee job satisfaction. In addition, the result of hypothesis testing through t-test also showed that the significance level was 0,000 which was greater than 0.05, and it means partially the democratic leadership style had a significant effect on employee job satisfaction.Keywords: Democratic leadership style, Employee job satisfaction, Humen resource management